När samtycke saknas - Rättsliga möjligheter till psykiatrisk respektive somatisk tvångsvård av patienter med nedsatt beslutsförmåga - Eckerdal,Julia (2025)
The patient’s right to self-determination is an important principle within Swedish healthcare. As a general rule, according to chapter 4, section 2 of the Patient Act (2014:821), healthcare may only be provided after obtaining consent from the patient. There are certain exceptions to this rule, but the possibilities for providing care without the patient’s consent differ between psychiatric and somatic care. Within the psychiatric field, involuntary care may be provided under the Act (1991:1128) on Compulsory Psychiatric Care. There is no equivalent legislation within the field of somatic care. However, somatic care may be provided in certain emergency situations according to chapter 4, section 4 of the Patient Act and chapter 24, section 4 of the Penal Code. The purpose of this essay is to investigate the legal possibilities for providing somatic care to patients with impaired decision-making ability, despite the absence of consent. Furthermore, it aims to examine how the legal possibilities for psychiatric and somatic compulsory care differ. The study has been conducted using a legal dogmatic method. One of the conclusions drawn from the study suggests that the legal position is unclear regarding the scope of application of chapter 4, section 4 of the Patient Act and chapter 24, section 4 of the Penal Code. It is also unclear to what extent somatic involuntary treatment may be provided under the Act on Compulsory Psychiatric care. Moreover, it is noted that there is a lack of clear guidance on what is required for the consent of the patient to be considered valid and how patients with impaired decision-making ability should be treated within health care. Against this background, a wide margin is left to the healthcare professionals to make discretionary decisions, leading to a lack of predictability regarding the scope of application of the rules.
Keywords: socialrätt; medicinsk rätt; tvångsvård